Pelatihan dan Sosialisasi Inovasi Produk dan Pencatatan Keuangan Menggunakan Aplikasi Lamikro Dalam Meningkatkan Home Industri Masyarakat Kelurahan Sekip Pekanbaru - Ibrahim, Mariaty; Etika, Etika; Nurita, Riau; Yulia, Nur Arini; Farhan, Muhammad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Sekip Village is one of the urban villages located near the center of Pekanbaru City that has great potential for the development of the creative economy sector. However, the products offered by business actors in this area remain limited in terms of innovation and are not yet optimally managed in the financial aspect. This community service activity aims to enhance the attractiveness of business products through product innovation and to implement financial recording using a simple digital financial application (Lamikro) for business actors, as an effort to increase consumer purchase interest and business financial sustainability. The methods used in this activity include socialization, training, and mentoring, which are focused on two main aspects: the development of culinary product innovation (taste, packaging, and branding) and the strengthening of basic financial recording using the Lamikro application. The participants of the activity consisted of culinary MSME actors in Sekip Village. The results of the activity indicate an improvement in participants' knowledge and skills in developing more attractive products as well as more structured financial records. Product innovation and financial recording have proven to be an effective combination in increasing product competitiveness and encouraging consumer purchase interest in businesses in Sekip Village, Pekanbaru. This activity is expected to contribute to strengthening the local economy based on cultural wisdom.